Life After AREDS 2: What Should We Recommend to Patients With or at Risk of AMD? - Michaud, Langis; Brûlé, Julie; Dufour, Jean-Sebastien; Forcier, Pierre; Fortin, Guillaume; Messier, Kevin; Rhéaume, Marc-André; Rhéaume, Yvon; Simard, Patrick; Clark, Christina (Canadian Journal of Optometry, 2014)
Purpose: To establish a consensus on clinical recommendation of oral supplementation for patients with or at risk of developing age-related macular degeneration (AmD), from the perspective of the Age-Related eye Disease Study 2 (AReDS 2) and other studies. Methods: Panel discussion based on a literature review of pertinent articles related to the prevention of AmD with oral supplementation. Results: on the basis of the findings, patients must first be encouraged to modify their diet and to eliminate modifiable risk factors before being recommended any type of oral supplementation. Then, recommendations must be customized on the basis of a patient’s individual risk profile (i.e., age, gender, heredity, etc.) and severity of disease (i.e., category 1 to 4). essential fatty acids (omega-3s) and vitamins may play a role, in a given clinical population, to prevent the occurrence or the progression of AmD disease. However, there is no single formula that can be applied to all patients with or at risk of AmD. Conclusions: This group concluded that the full body of literature must be taken into consideration in order to justify clinical recommendations for patients. A single study such as AReDS 2 cannot, by itself, guide clinical practice. In all cases, recommendations must be individualized and patients should be monitored regularly.